Zygmunt Grudziński, 1870–1929 - Sudoł-Szopińska, Iwona; Panas-Goworska, Marta; Szczerbo-Trojanowska, Małgorzata (Seminars in Musculoskeletal Radiology, 2023)
This history page in the series “Leaders in MSK Radiology” is dedicated to the memory and achievements of Zygmunt Grudziński, Polish radiologist at the University of Warsaw and founder of the Polish Society of Radiology and Polish Radiological Review, the first radiology journal.
Keywords: Zygmunt Grudziński; radiology; history; pioneer